(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the composition, resource potential, and role of the Tashkent economic region in the national economy of Uzbekistan. Encompassing the city of Tashkent and Tashkent region, this economic area holds a leading position in the country’s industry, transport, trade, services, and agro-industrial sectors. The article also highlights the region’s strategic importance through its labor resources, scientific centers, and infrastructure capacity. Based on the analysis, the decisive role of the Tashkent economic region in the economic development of Uzbekistan is substantiated.